The oxygen isotopic composition (18O/16O) in the dust of comet 67P/Churyumov-Gerasimenko measured by COSIMA on-board Rosetta. Issue 3 (13th March 2018) - Paquette, J A; Engrand, C; Hilchenbach, M; Fray, N; Stenzel, O J; Silen, J; Rynö, J; Kissel, J; ,
Abstract: The oxygen isotopic ratio 18 O/ 16 O has been measured in cometary gas for a wide variety of comets, but the only measurements in cometary dust were performed by the Stardust cometary sample return mission. Most such measurements find a value of the ratio that is consistent with Vienna Standard Mean Ocean Water (VSMOW) within errors. In this work we present the result of a measurement, using the COSIMA (the COmetary Secondary Ion Mass Analyser) instrument on the Rosetta orbiter, of the oxygen isotopic ratio in dust from Comet 67P/Churyumov-Gerasimenko. Measuring the 18 O/ 16 O ratio with COSIMA is challenging for a number of reasons, but it is possible with a reasonable degree of precision. We find a result of 2.00 × 10 −3  ± 1.2 × 10 −4, which is consistent within errors with VSMOW.